Usability Testing on Tracer Study System Using The Heuristic Evaluation Method - Afriansyah Afriansyah; Walhidayat Walhidayat; Rizki Novendra; Lidwina Harefa; Sutejo Sutejo (Journal of Applied Engineering and Technological Science (JAETS), 2022)
A tracer study is a survey of graduates tracks alumni activities after graduating from an educational institution, Lancang Kuning University is one of the educational institutions that have a tracer study system. A system can be said to be good if it has good usability. So the purpose of this research is to find out whether the tracer study system of Universitas Lancang Kuning has good usability. The heuristic evaluation method will be used to measure usability using 10 aspects of usability heuristics with a questionnaire media in collecting data. Before distributing the questionnaires, an instrument test such as the Gregory test will be carried out by involving system experts and linguists. Then a validity test will be carried out, a reliability test will be carried out after that a heuristic test is carried out by distributing questionnaires. Based on the calculation results that the lowest percentage is owned by the visibility of the system status variable by 75% and the highest percentage results in the match between the system and the real world and consistency and standard with the same calculation results obtained by 81%. The results of the analysis show that the tracer system of Universitas Lancang Kuning has high usability with an average percentage of 78%.